Experimental study of bone drilling by Kirschner wire. (August 2022) - Song, Shaokang; Cheng, Xiang; Li, Tao; Shi, Ming; Zheng, Guangming; Liu, Huanbao
Highlights: Simulation model of bone drilling is established. Influences of Kirschner wire beveled angle, rotational speed, and feed rate on drilling force and drilling temperature is discussed. Influence of bone chips on drilling force and drilling temperature is explored. Micro-burr at the entrance of the hole is detected and analyzed. Process parameters are optimized to achieve the low bone damage. Abstract: Mechanical and thermal damage to the bone tissue during drilling process is inevitable and directly affects the postoperative recovery. According to clinical practices and present academic investigations, this study tries to reduce bone damage by experimental investigation of bone drilling by Kirschner wire considering the drilling force and temperature factors. Finite element method has been applied to modelling of the drilling process. Then, grouped experiments have been carried out using bovine femoral bone and analyzed based on the orthogonal experimental method. The influence of key parameters such as Kirschner wire bevel angle, feed speed and rotational speed on the microscopic bone chip size, drilling force, drilling temperature and hole inlet burr was analyzed to conduct comprehensive analysis and optimizations. It is certain that the chips size is closely related to drilling force and drilling temperature. The low drilling temperature does not mean that the damage area is small. The drilling process should be completed quickly at high feed rates. The lower rotational speed, Kirschner wire bevel angle, and higher feed rate help reduce the thermal damage area of the bone drill, effectively reduce the drilling force and hole entrance burrs.